If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (B + -2) + (B) + (B + 3) = 25 Reorder the terms: (-2 + B) + (B) + (B + 3) = 25 Remove parenthesis around (-2 + B) -2 + B + (B) + (B + 3) = 25 -2 + B + B + (B + 3) = 25 Reorder the terms: -2 + B + B + (3 + B) = 25 Remove parenthesis around (3 + B) -2 + B + B + 3 + B = 25 Reorder the terms: -2 + 3 + B + B + B = 25 Combine like terms: -2 + 3 = 1 1 + B + B + B = 25 Combine like terms: B + B = 2B 1 + 2B + B = 25 Combine like terms: 2B + B = 3B 1 + 3B = 25 Solving 1 + 3B = 25 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3B = 25 + -1 Combine like terms: 1 + -1 = 0 0 + 3B = 25 + -1 3B = 25 + -1 Combine like terms: 25 + -1 = 24 3B = 24 Divide each side by '3'. B = 8 Simplifying B = 8
| 6-1/4=C | | -8+x=-4+0 | | ln(x+9)-ln(x-9)= | | y+10+6y=180 | | 10=.006X^2-.02X | | ln(x+9)+ln(x-9)= | | (x+2)(x-2)-45=0 | | 5(5x+8)=13-(2x+5) | | 1-81x^2= | | -3x^2-5x-2=0 | | 4d+4=0 | | 19+p=18 | | (x+7)(x+11)=1 | | b/2-5=51/2 | | 19c+31=26c+74 | | (B*2)+(B)+(B*2+1)=76 | | -4y+7=11 | | 4.8x-60=2.6x+6 | | 11x+1=-1+x | | 72/(40x-8) | | 25t-4=1+25t | | (x+7)(x+11)=0 | | 54x^2/(30x^2+12x) | | 6-5x=7x+6 | | (w*7)-2=60 | | -6x^2+9x+7=0 | | 2z+5-5=z-5 | | 2x+14=49+14x+x^2 | | (7w)-2=60 | | ln(x+5)-ln(5)=ln(20) | | 5t-4=1+25t | | -6d^2+3cd+c-2d= |